Safety notices and registry outlier data measure different aspects of safety and performance of total knee implants: a comparative study of safety notices and register outliers - Lotje A Hoogervorst; Yijun Ren; Tom Melvin; Ashley A Stratton-Powell; Anne Lübbeke; Robert E Geertsma; Alan G Fraser; Rob G H H Nelissen; Enrico G Caiani; Perla J Marang-van de Mheen (Acta Orthopaedica)
Background and purpose: Safety notices for medical devices such as total knee arthroplasty (TKA) implants may indicate problems in their design or performance that require corrective action to prevent patient harm. Safety notices are often published on national Ministries of Health or regulatory agencies websites. It is unknown whether problems triggering safety notices identify the same implants as those identified by registries as “outlier.” We aimed to assess the extent to which safety notices and outlier identification in registries signal the same or different TKA implants. Methods: The CORE-MD tool, an automated web scraper tool, was used to collect safety notices related to TKA implants on 13 national Ministries of Health websites and regulatory agencies. Safety notices were defined according to the Medical Device Regulation (MDR) as “a communication sent by a manufacturer to users or customers in relation to a field safety corrective action.” Identified TKA outliers, defined as having a significantly higher revision risk than other comparable TKA implants, were extracted from registry reports. Results: 787 safety notices for 38 TKA implants and 35 TKA outliers were identified, together identifying 47 unique TKA implants. 26 (55%) TKA implants had safety notices and were also outliers, 12 (26%) TKA implants had only safety notices, and 9 (19%) were outliers only. TKA implants with safety notices only had similar types of problems to TKA outliers with safety notices, with “Manufacturing/Packaging/Shipping” problems being most frequent (44%). Cumulative revision risks (1/5/10 years) were lower for TKA implants with safety notices only than for TKA outliers with safety notices. Conclusion: 55% of the TKA with a safety notice were identified as outliers in the registry, whereas around 25% of TKA outliers are not the subject of publicly released safety notices, with safety notices pointing to TKA implants not identified by registries as potentially having a higher risk of failure. This suggests that safety notices and registry outlier data measure different aspects of safety and performance.